2005
DOI: 10.1093/aje/kwh331
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Breast Cancer Risk Factors among African-American Women and White Women

Abstract: The authors assessed risk factor profiles among 1,505 African-American and 1,809 White women in the 1993-2001 Carolina Breast Cancer Study. Multiple logistic regression models for case-control data were used to estimate odds ratios for several factors. Racial differences were observed in the prevalence of many breast cancer risk factors among both younger (aged 20-49 years) and older (aged 50-74 years) women. For older women, the magnitude and direction of associations were generally similar for African-Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
96
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(108 citation statements)
references
References 26 publications
8
96
2
2
Order By: Relevance
“…Our results confirmed that nonreactivity of hormonal receptors increases with increase in tumor size. Infiltrating ductal carcinoma was the most common histological type similar to other studies followed by medullary carcinoma in our study where as in other studies Infiltrating lobular carcinoma being the second most common type [14,15] . Our study provides convincing evidence for a non-significant association between expression of ER, PR and lymph node metastasis.…”
Section: Discussionsupporting
confidence: 90%
“…Our results confirmed that nonreactivity of hormonal receptors increases with increase in tumor size. Infiltrating ductal carcinoma was the most common histological type similar to other studies followed by medullary carcinoma in our study where as in other studies Infiltrating lobular carcinoma being the second most common type [14,15] . Our study provides convincing evidence for a non-significant association between expression of ER, PR and lymph node metastasis.…”
Section: Discussionsupporting
confidence: 90%
“…There is some evidence to suggest that, unlike the protective effect of pregnancy on breast cancer risk among women after age 45, early childbearing and higher birth rate observed among black women could increase the likelihood of higher incidence of premenopausal breast cancer [28][29][30] . Moreover, among younger black women, multiparity 31 coupled with lower likelihood of lactation and shorter duration of lactation 32 may also contribute to a higher incidence rate. The reduction in modifiable risk factors including, hormone replace therapy, alcohol consumption, physical activity, and duration of breast-feeding, could substantially reduce breast cancer incidence 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Among controls, the median time interval between date of ascertainment (sampling) and date of interview was 3.8 months (mean, 6.4 months), and 90% of interviews occurred within 15 months of ascertainment. CBCS participant characteristics were reported previously (33)(34)(35). Race was classified according to self-report.…”
Section: Methodsmentioning
confidence: 99%